Effect of intraspecific competition between larvae of Calliphora erythrocephala (Meig.) (Calliphoridae, Diptera). - Shahein, Ali (Contributions to Entomology = Beiträge zur Entomologie, 1986)
Competition for food among larval population of C. erythrocephala (Meig.) constitutes an importand factor limiting the general fly population in nature. This factor is true since the primary factor which limits the abundance of any insect population in the quantity of food which is available to it within its given universe. - Investigation about the influence of intraspecific competition of this species during the larval growth were carried out to asses the following criteria: average weigth of pupae; % of pupation; % of mortality the larvae; % of emergence; sex ratio and number of ovarioles.